1990
DOI: 10.1037/0278-7393.16.4.617
|View full text |Cite
|
Sign up to set email alerts
|

Roles of function, reminding, and variability in categorization by 3-month-old infants.

Abstract: The roles of function, reminding, and exemplar variability in categorization of a physically dissimilar object were studied with 3-month-old infants trained to move a crib mobile by kicking. Performance on a transfer test with a motionless novel object provided evidence of categorization. In Experiments 1 and 2, infants, like adults, initially categorized novel objects on the basis of physical appearance, but only if trained with multiple exemplars, after delays of 1 and 7 days. In Experiment 3, prior knowledg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

23
120
1

Year Published

1993
1993
2005
2005

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 94 publications
(144 citation statements)
references
References 87 publications
(161 reference statements)
23
120
1
Order By: Relevance
“…The same finding had been obtained by Greco et al (1990) when, following variable training, they had exposed infants to a stationary object that bore no physical resemblance to the training mobiles. Greco et al found that the highly physically dissimilar object was integrated with the prior training memory, however, if they exposed infants to information about the object's function (movement), which it shared with the prior training exemplars.…”
Section: Methodssupporting
confidence: 60%
See 3 more Smart Citations
“…The same finding had been obtained by Greco et al (1990) when, following variable training, they had exposed infants to a stationary object that bore no physical resemblance to the training mobiles. Greco et al found that the highly physically dissimilar object was integrated with the prior training memory, however, if they exposed infants to information about the object's function (movement), which it shared with the prior training exemplars.…”
Section: Methodssupporting
confidence: 60%
“…Although Greco et al (1990) had found that the attributes of a novel object were not integrated with the prior training memory unless it was exposed in motion-a function it shared with the category-training exemplars-we thought that information about shared function might not be necessary because the novel mobile to which infants would be passively exposed more closely resembled the training mobile than that used in the earlier study.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Of particular interest for the present study is the consistent finding that infants' forgotten memory of one event is reactivated when their forgotten memory of a second, associated event is primed (Greco, Hayne, & Rovee-Collier, 1990; Rovee-Collier, Sheffield & Hudson, 1994;Timmons, 1994). Timmons, for example, trained 6-month-old infants to move a mobile by foot kicking and then to turn on a music box by arm waving, or vice versa (mobile-arm wave, music box-footkick).…”
mentioning
confidence: 99%